공간 벡터 변조 방식을 이용한 개방 권선형 매입형 영구자석 동기 전동기의 전압 각 기반 토크 예측 제어 - 윤태용 (The Graduate School, Ajou University, 2024)
This thesis proposes predictive torque control (PTC) based on voltage angle using the space vector modulation (SVM) method for driving an open-end winding interior permanent magnet synchronous motor (OEW-IPMSM) fed by a dual inverter. Conventional predictive torque control (Conv-PTC) has the advantages of fast dynamic response and simple algorithm structure. However, Conv-PTC has drawbacks in terms of torque and current quality, since the voltages are applied within limited voltage vectors, which have real switching states. The proposed predictive torque control with space vector modulation (PTC-SVM) method provides various virtual voltage vectors generated near the estimated voltage angle. A number of virtual voltage vectors give an effect for selecting optimal values to follow the reference torque, flux, or currents. Furthermore, voltage vectors generated based on the voltage angle not only reduce steady-state errors but also allow for fewer calculation numbers to be maintained. The effectiveness of the proposed PTC using the SVM method for driving OEW-IPMSM is proved by simulation and experimental results compared to Conv-PTC.
학위논문(석사)--전자공학과,2024. 2
Keywords: open-end winding interior permanent magnet synchronous motor (OEW-IPMSM); perdictive torque control (PTC); predictive torque control with space vector modulation (PTC-SVM); space vector modulation (SVM); torque ripple reduction